(untitled) (Journal of Patan Academy of Health Sciences, 2025)
Professor Dr. Arjun Karki, the founding Vice-Chancellor of the Patan Academy of Health Sciences (PAHS), is a distinguished Nepali physician, academic, and institutional leader. He is widely recognized for his contributions to pulmonary and critical care medicine, as well as for his transformative role in advancing higher education reform in Nepal. Dr. Karki spearheaded initiatives to embed innovative, student-centered, and socially responsive approaches into medical education, notably introducing mandatory rural health postings to foster community engagement and equity in healthcare delivery. His leadership has been instrumental in institution-building and in nurturing a robust education & research ecosystem within the country. Currently serving as the Vice-Chancellor of the University of Nepal, Dr. Karki continues to exemplify his enduring commitment to educational reform and institutional excellence. The Journal of Patan Academy of Health Sciences extends its sincere gratitude to Dr. Karki for his generous and thoughtful engagement in responding to the written questions prepared for this interview.